Identifying matrix metalloproteinase-12 substrates as therapeutic targets in chronic obstructive pulmonary disease - Mallia-Milanes, Brendan (2015)
Chronic Obstructive Pulmonary Disease (COPD) is the third commonest cause of death worldwide. Its natural course is a decline in lung function, punctuated by exacerbations, leading to premature death. COPD pathogenesis remains incompletely understood. The disease is widely accepted to result from an excess protease over protective anti-protease activity, leading to extracellular matrix (ECM) damage in the lungs. However, this belief is oversimplified since both harmful pro-inflammatory and protective anti-inflammatory roles are now described for proteases in animal and cell culture models. Matrix Metalloproteinase (MMP)-12 was originally implicated in COPD by its degradation of elastin in the lung ECM. However, newer in vitro evidence reveals MMP-12 to target substrates outside the ECM. Given these newer findings it was hypothesized that MMP-12 cleaves non-ECM proteins in COPD which may contribute to the disease process. This hypothesis was addressed initially using a candidate-based approach, by testing osteopontin and tissue factor pathway inhibitor as potential MMP-12 substrates. However, these proved to be neutrophil elastase targets. Next, a novel proteomic technique called TAILS (Terminal Amine Isotopic Labelling of Substrates) was employed to identify potential MMP-12 substrates using a Mmpl2-/-smoking mouse model. This led to the discovery of new non-ECM MMP-12 substrates in the mouse model. Next, these findings were translated to human COPD sputum to identify potential MMP-12 targets in COPD, both at exacerbation and during stable disease. Similarly, within human COPD sputum non-ECM MMP-12 substrates were discovered, of particular interest, complement factor C3 and the anticoagulant anti-thrombin III, revealing ever new potential roles for MMP-12 in COPD.